The effect of encapsulation on the in vitro anti-oxidative activity of rutin - Pensak Jantrawut (2018)
Objective: This study was investigating the effect of encapsulation on the in vitro anti-oxidative activity of rutin. Methods: Rutin encapsulated in non-amidated low methoxyl pectin bead in various formulations with or without sorbitol and/or sodium bicarbonate (NaHCO3 Results: The rutin encapsulated in 3NA15Sor1Bica (3% non-amidated LMP with 15% sorbitol and 1% NaHCO) were prepared as well as in vitro anti-oxidative assays including 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging, chelating, lipid peroxidation inhibition and 2,2'-azinobis-3-ethylbenthiazoline-6-sulfonic acid (ABTS) radical cation decolorization were investigated. 3 Conclusion: The results from this study can be applied for the further development of the encapsulation formulation by adding the suitable proportion of sorbitol and NaHCO) beads showed anti-oxidative activity higher than the other formulations on DPPH radical scavenging (84.00 ± 4.47%), chelating (74.11 ± 4.29%) and ABTS radical cation decolorization (80.04 ± 7.93%) activities. 3 in order to maintain the activities of encapsulated compounds.